Minaret - Aboulela, Leila, 1964- (New York : Grove Press, 2005)
Leila Aboulela's American debut is a provocative, timely, and engaging novel about a young Muslim woman
Keywords: Sudanese -- Great Britain -- Fiction; Political refugees -- Fiction; Women household employees -- Fiction; Muslim women -- Fiction; Rich people -- Fiction; Orphans -- Fiction; London (England) -- Fiction; Love stories